An information system and medical record to support HIV treatment in rural Haiti. Issue 7475 (11th November 2004) - Fraser, Hamish S F; Jazayeri, Darius; Nevil, Patrice; Karacaoglu, Yusuf; Farmer, Paul E; Lyon, Evan; Fawzi, Mary Kay C Smith; Leandre, Fernet; Choi, Sharon S; Mukherjee, Joia S
Abstract : Lack of infrastructure, including information and communication systems, is considered a barrier to successful HIV treatment programmes in resource poor areas. The authors describe how they set up a web based medical record system linking remote areas in rural Haiti and how it is used to track clinical outcomes, laboratory tests, and drug supplies and to create reports for funding agencies